In vitro inhibition effect and structure–activity relationships of some saccharin derivatives on erythrocyte carbonic anhydrase I and II. (February 2014) - Sonmez, Fatih; Bilen, Cigdem; Sumersan, Sinem; Gencer, Nahit; Isik, Semra; Arslan, Oktay; Kucukislamoglu, Mustafa
Abstract In this study, in vitro inhibitory effects of some saccharin derivatives on purified carbonic anhydrase I and II were investigated using CO2 as a substrate. The results showed that all compounds inhibited the hCA I and hCA II enzyme activities. Among the compounds, 6-(p-tolylthiourenyl) saccharin (6m) was found to be the most active one for hCA I activity (IC50 = 13.67 μM) and 6-(m-methoxyphenylurenyl) saccharin (6b) was found to be the most active one for hCA II activity (IC50 = 6.54 μM). Structure–activity relationships (SARs) study showed that, generally, thiourea derivatives (6l--v) inhibited more hCA I and hCA II than urea derivatives (6a–k). All compounds (excluding 6c and 6r) have higher inhibitory activity on hCA II than on hCA I.